The influence of mentalization and psychological flexibility on the mental health of graduate students in China: a cross-sectional study - Wang, Xinghua; Yang, Xiaosha; Li, Xuemei (Frontiers in Psychiatry, 2025)
BackgroundPsychological health problem has become an important health problem of graduate students worldwide. Mentalization and mental flexibility are important factors related to mental health, but their relationship has not been discussed before in graduate students. The purpose of this study was to evaluate the mental health status of postgraduates and to determine whether mentalization and psychological flexibility are significant factors affecting the mental health status of postgraduates.Methodssamples of the communist party of China, there are 2728 graduate students. GAD-7, PHQ-9 were used to assess mental health. Mind through mental questionnaire (MZQ) measure, the Acceptance and Action Questionnaire 2nd Edition (AAQ-II) and Cognitive Fusion Questionnaire (CFQ-F) to evaluate mental flexibility. Multiple factors analysis and linear regression analysis is used to determine the Mentalization, the mental flexibility and the relationship between the participants’ mental health.ResultsThere were significant differences in the scores of anxiety and depression in gender, residence, left-behind experience, and parents’ marital status. The scores of the four dimensions of mentalization were positively correlated with the scores of anxiety. In mentalization, MZQ-refusing self-reflection, MZQ-emotional awareness, MZQ-emotional regulation score and depression score were positively correlated. Psychological flexibility played a partial mediating role in the four dimensions of mentalization and anxiety scores. The mediating effect of cognitive fusion was not clear in the four dimensions of mentalization and depression scores. Acceptance and action played a partial mediating role in refusing self-reflection, emotional awareness, and regulation of affect, as well as a full mediating role in psychic equivalence mode and depression scores.ConclusionsMentalization and psychological flexibility are significantly correlated with anxiety and depression in graduate students. The four dimensions of mentalization and psychological flexibility exhibit varying degrees and linear relationships with graduate students’ anxiety and depression. In the relationship between mentalization and anxiety-depressive emotions, the mediating effects of acceptance and behavior, as well as cognitive fusion, are different. This suggests that investigating mentalization and psychological flexibility in relation to anxiety and depression is meaningful. Mentalization and psychological flexibility may potentially serve as important indicators of graduate students’ mental health in the future.